Elementary Earth and Space Science Methods - Neal, Ted (Open textbook library., 2019)
We created this book to help you as both a college student and a future teacher. Dr. Ted Neal asked us to help him create this resource from the perspective of students who have taken Science Methods II–what would we want in a textbook for this course? With this in mind, we have gathered and created resources to help you better understand science and feel confident in your abilities as a future teacher. This book is divided into five parts which align with the Science Methods II course: Physics Space Science Earth Science Climate Science Course Materials and Pedagogy Within each part, the material is broken down into smaller chapters. Here you will find written explanations, video links, glossary terms, key takeaways, and practice quizzes to help you understand the material. This book is designed to be a flexible resource; use it as much or as little as you need throughout the course.